Case review of ocular scedosporiosis - Alok Agrawal; Mainak Raychaudhuri (Wolters Kluwer Medknow Publications, 2021)
Fungal keratitis is one of the leading cause of corneal blindness especially in developing countries like India. It requires prompt diagnosis and vigorous management as early as possible. Any delay in the initial period can have severe consequences on the quality of life of the patient. This often happens in a patient who is immunocompromised and is therefore slow to respond to treatment. However, as evident from this article, even an immunocompetent patient can prove to be a challenging case, especially if the causative organism is a rare filamentous fungi like Scedosporium apeospermum.